Dendritic porphyrin-fullerene conjugates: Efficient light-harvesting and charge-transfer events - Schlundt, Sebastian; Kuzmanich, Gregory; De Miguel Rojas, Gustavo; Kovács, Christian; Garcia-Garibay, Miguel A.; Guldi, Dirk Michael; Hirsch, Andreas; et al. (Chemistry - A European Journal, 2009)
A novel dendritic C-HP(ZnP) (P = porphyrin) conjugate gives rise to the successful mimicry of the primary events in photosynthesis, that is, light harvesting, unidirectional energy transfer, charge transfer, and charge-shift reactions. Owing, however, to the flexibility of the linkers that connect the Q, HP, and ZnP units, the outcome depends strongly on the rigidity/viscosity of the environment. In an agar matrix or Triton X-100, timeresolved transient absorption spectroscopic analysis and fluorescence-lifetime measurements confirm the following sequence. Initially, light harvesting is seen by the peripheral C-H P-*(ZnP) conjugate. Once photoexcited, a unidirectional energy transfer funnels the singlet excited-state energy to HP to form C-*(HP)-(ZnP), which powers an intramolecular charge transfer that oxidizes the photoexcited HP and reduces the adjacent C species. In the correspondingly formed (C)'(HP) -(ZnP) conjugate, an intramolecular charge-shift reaction generates (C)-HP-(ZnP) , in which the radical cation resides on one of the three ZnP moieties, and for which lifetimes of up to 460 ns are found. On the other hand, investigations in organic media (i.e., toluene, THF, and benzonitrile) reveal a short cut, that is, the peripheral ZnP unit reacts directly with C to form (C)H P-(ZnP) . Substantial configurational rearrangements-placing ZnP and C in proximity to each other-are, however, necessary to ensure the required through space interactions (i.e., close approach). Consequently, the lifetime of (C)'"-H P(ZnP) is as short as 100 ps in benzonitrile. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA,.

Synthesis and Atropisomerism of Cascaded Tetraphenylporphyrin-[60]Fullerene Hybrids - Schlundt, Sebastian; Bauer, Walter; Hirsch, Andreas (Chemistry - A European Journal, 2015)
Keywords: atropisomerism; dendrons; fullerenes; metallocenes; porphyrinoids